Respuesta :

Answer: A

Step-by-step explanation:

4( 1 - x) + 2x = -3(x + 1)

4 - 4x + 2x = -3x - 3               Distribute numbers to paranthesis

4 - 2x = -3x - 3                       Add like terms

4 + x = -3                                Add 3x to both sides

x = -7                                       subtract 4 to both sides

Answer:

hi

Step-by-step explanation:

thanks for my points back when u went to my post and didnt answer and said free points so ty for the oints back i hate people like u ur so rude bruh

ACCESS MORE